SURVEY TENTANG MASALAH-MASALAH YANG DIHADAPAI OLEH SISWA KELAS VIII SMP NEGERI 1 INUMAN - Dasmaniar Dasmaniar (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is a survey research about the problems faced by students of grade VII SMP Negeri 1 Inuman. Theresults of this study were: (a) on the indicators of students who felt themselves problematic about the health of33 people (33.33%); (b) on indicators of students who feel themselves problematic about the family economythat is 30 people (35.71%); (c) on the indicators of students who feel themselves problematic parenting in thefamily that is 31 people (36.90%); (d) on indicators of students who feel themselves problematic about peerrelationships that is 21 people (25.00%); (e) on the indicator of students who feel themselves problematic aboutusing leisure / leisure which is 44 people (52.38%); (f) on indicators of students who feel themselves problematicabout the future ie 58 people (69.04%); (g) on indicators of students who feel themselves problematic about selfconfidence that is 31 people (36.90%); (h) on indicators of students who feel themselves problematic about themotivation to learn that is 17 people (20.33%); (i) in the indicator of students who feel themselves problematicabout the relationship with the teacher that is 27 people (32.14%); (j) on indicators of students who feelthemselves problematic about the opposite sex that is 16 people (19.04%); (k) on indicators of students who feelthemselves problematic about the opposite sex that is 16 people (19.04%); and (l) on the indicator of studentswho feel themselves problematic about the relationship with school life that is 21 people (25.00%).